2015
DOI: 10.7554/elife.08648
|View full text |Cite
|
Sign up to set email alerts
|

A deleterious gene-by-environment interaction imposed by calcium channel blockers in Marfan syndrome

Abstract: Calcium channel blockers (CCBs) are prescribed to patients with Marfan syndrome for prophylaxis against aortic aneurysm progression, despite limited evidence for their efficacy and safety in the disorder. Unexpectedly, Marfan mice treated with CCBs show accelerated aneurysm expansion, rupture, and premature lethality. This effect is both extracellular signal-regulated kinase (ERK1/2) dependent and angiotensin-II type 1 receptor (AT1R) dependent. We have identified protein kinase C beta (PKCβ) as a critical med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
80
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 37 publications
(50 reference statements)
3
80
0
Order By: Relevance
“…Marfan patients who received CCB (n=531) prior to or at the time of their diagnosis (followed up for a mean time of 50.8±1.6 months), when compared to groups not taking CCBs, were found more likely to have acute aortic dissections [odds ratio (OR) =12.5; P=0.032] (32). Patients on CCBs had greater odds of having surgery than those on other hypertensive regimens (OR =5.5, P=0.001) (32). Findings from this study revealed that patients on amlodipine had worse outcomes than those taking verapamil, which may be explained by the known selectivity of verapamil for cardiac tissue (32).…”
Section: Ccbsmentioning
confidence: 53%
See 2 more Smart Citations
“…Marfan patients who received CCB (n=531) prior to or at the time of their diagnosis (followed up for a mean time of 50.8±1.6 months), when compared to groups not taking CCBs, were found more likely to have acute aortic dissections [odds ratio (OR) =12.5; P=0.032] (32). Patients on CCBs had greater odds of having surgery than those on other hypertensive regimens (OR =5.5, P=0.001) (32). Findings from this study revealed that patients on amlodipine had worse outcomes than those taking verapamil, which may be explained by the known selectivity of verapamil for cardiac tissue (32).…”
Section: Ccbsmentioning
confidence: 53%
“…Ann Cardiothorac Surg 2017;6(6):654-661 www.annalscts.com Recent animal studies demonstrated a detrimental effect of CCB on Marfan mice, as mice treated with CCBs exhibited higher rates of dissection on 3-month follow-up compared to those given placebo (32). This discovery was also found to have relevance in humans, as retrospective trials of CCB agents aiming to evaluate adverse outcomes displayed similar results.…”
Section: Ccbsmentioning
confidence: 56%
See 1 more Smart Citation
“…8 While studying the ability of various classes of antihypertensive agents to modify the aneurysm phenotype in mouse models of Marfan syndrome, we observed that calcium channel blockers unexpectedly led to hyperacute acceleration of aneurysm growth and tear, literally tripling aneurysm size within 5 weeks and causing death due to aortic rupture within 6 weeks of treatment initiation. Mechanistic characterization led to appreciation of a pathogenic role for the PLC-IP3-PKC axis and a protective role for the PKC inhibitor enzastaurin in Marfan mice that had-or had not-received calcium channel blockers.…”
mentioning
confidence: 99%
“…Surprisingly, first in the mouse model treated with either amlodipine or verapamil, and subsequently in retrospective analysis of humans, calcium-channel blockade was found to be harmful, probably through protein kinase C (PKC) activation (23). Interestingly, hydralazine inhibits PKC and might be an alternative therapy for those patients who cannot tolerate β-blockade or AT1 blockade.…”
mentioning
confidence: 99%